The Leading-Edge Structure Based on Geometric Bionics Affects the Transient Cavitating Flow and Vortex Evolution of Hydrofoils - Yan, Hao; Zhang, Haozhou; Wang, Junhua; Song, Tianya; Qi, Fenglei (Frontiers in Energy Research, 2022)
A hydrofoil is a fundamental structure in fluid machinery, and it is widely applied to the fields of propellers, blades of axial flow pumps and underwater machinery. To reveal that the geometric structure of the leading-edge of a hydrofoil is the mechanism that affects the transient cavitating flow, we regard the three fish-type leading-edge structures of mackerel, sturgeon and small yellow croaker as the research objects and use high-precision non-contact 3D scanners to establish three bionic hydrofoils (Mac./Stu./Cro.). We use large eddy simulation to simulate the transient cavitating flow of hydrofoils numerically and compare and analyze their lift–drag characteristics, the transient behavior of unsteady cavitation and the vortex evolution. The numerical simulation results are in good agreement with the experimental results. The warping of leading-edge structure will cause a change in lift–drag characteristics, and the Cro. hydrofoil has a good lift-to-drag ratio. When the leading-edge structure is tilted upward (Cro. hydrofoil), the position of the attached cavity will move forward, which will accelerate the cavitation evolution and improve the velocity fluctuation of the trailing edge. When the leading-edge structure is tilted downward (Stu. hydrofoil), the change in the vortex stretching and dilatation terms will be complex, and the influence area of the vortex will widen.